The "shape" of interaction networks on Twitter. (September 2018) - Findlay, Kyle
This article is concerned with qualitative descriptions of the morphological structure of Twitter interaction network topologies. It summarizes learnings gleaned from mapping numerous brand, category, and campaign interaction networks on Twitter. The article characterizes the different network "shapes, " or typologies, that emerge from discussions about brands, campaigns, and categories and places these shapes on a continuum from highly centralized to highly decentralized. The article discusses how brands might strategically and tactically use these insights to maximize their communications and brand building. This article is a substantially altered version of an article that was originally presented at the ESOMAR Congress conference in Dublin, Ireland, in September 2015.